THE EMPLOYEE MOTIVATION – THE KEY FACTOR IN BUSINESS SUCCESS (International Journal of Innovative Technologies in Economy, 2018)
We present you the work: “The Employee Motivation – the Key Factor in Business Success”, where we present the results of the research on this issue conducted by the universities of California and Stanford, based on which the author in cooperation with Batumi State Maritime Academy students made some enquiries in Batumi. Analysis of the survey revealed that if the managers are eager to keep the best employees, it is essential to consider them carefully and make an adequate use of their talent and extensive opportunities. Consequently, they must do their best in order to provoke qualified specialists’ desire to work with them, and in turn, to maximize the promotion of the business profit.